As contradições da sociedade punitiva: o delito de embriaguez ao volante - Guimarães, Jhulliem Raquel Kitzinger de Sena (2020)
The growing number of drunkenness crimes behind the wheel calls into question the effectiveness of the measures adopted by the Traffic Code in its more than 20 years of existence and four specific changes in the crime on screen and, consequently, the safety of those who walk or drive through the streets of the city. This dissertation study aims to understand the occurrence of drunkenness behind the wheel, in Amazonas, from the lawsuits collected in the System of Automation of Justice (SAJ), of the Court of Justice of the State of Amazonas seeking to unveil the discourses produced in the legal field about this type of crime. For the construction of the same, bibliographic research on the topic was carried out in books, articles, repositories of dissertations and theses to assist in the preparation of the literature review; and documentary research, with data collection of processes involving drunkenness behind the wheel that were judged by the TJAM, in the period from 2013 to 2019, whose speeches were analyzed under the aegis of the Foucaultian discourse. The five cases analyzed indicate that the crimes of drunk driving have several peculiarities, such as habitual drunkenness and varying degrees of education among the accused. The evidence produced in the procedural context is also varied, but there is a tendency among actors in the legal field to privilege those obtained through documentary over the testimonial, which in most cases is composed of police officers who approached the accused, still that they have public faith. There is still a contradiction as to the means of evidence when it comes to this crime, since the same evidence that is used to substantiate the complaint by the Public Prosecutor's Office, was once used by the same Ministerial body to request the acquittal of the accused, even under the circumstances of these were already known to him when the complaint was offered. It was also observed the plastering of judicial decisions, which despite portraying different cases with different circumstances and particularities, have the same average of penalties applied, with little commitment from the Court with effective changes in the treatment of the infraction that seek to curb the practice of the crime, among the options already available in the legal system, it can be seen that the power exercised by law is fundamentally anchored in symbolic power.